Sonography of the Primary Cutaneous Melanoma: A Review - Ximena Wortsman (Radiology Research and Practice)
The diagnosis and management of primary cutaneous melanoma have traditionally relied on clinical and histological characteristics. Nevertheless, in recent years there has been a significant growth in the usage of ultrasound for studying the cutaneous layers. Thus, the present paper focuses on the primary lesion, its sonographic characteristics, the potential benefits of early imaging, and the new developments on the ultrasound field applied to cutaneous melanoma.